Association of Gestational Diabetes and Childhood Obesity - Habibullah Babar, Shamayal Mandokhel, Zahida Kamal (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Maternal gestational diabetes is a commonly reported complication of pregnancy. Gestational diabetes has been highlighted as a risk of childhood obesity. There are various indicators which can assist in prediction of childhood obesity including waist circumference and body mass index measurements. Objective: To assess the relationship of gestational diabetes with childhood obesity. Study Design: Prospective comparative study Place and Duration of Study: Balochistan Institute of Child Health Services, Quetta from 1st March 2022 to 31st October 2023. Methodology: Four hundred children were enrolled, 200 children who were born to mothers with gestational diabetes while they were pregnant with the child under enrollment were termed as GDM group while the other 200 children who were born to mothers with no gestational diabetes during their pregnancy with the child under enrollment, were termed as non-GDM group Anthropometric data including stature/stature ratio, arm circumference, waist circumference, body mass, sitting height, body mass index, bioelectrical impedance was documented. The inclusion criteria of the study participants were based on the fact that either the obese child attending the OPD was born to a gestational diabetic mother or not. Children within the age of 6-12 years were included in the study. In addition to this child lifestyle including time for physical activity, sports, minutes of moderate-to-vigorous physical activity (MVPA), sedentary time, steps/day, diet and nutrition through food frequency chart were assessed. Results: The majority of children were boys with a percentage of 52% and 59% in non-GDMA and GDM groups respectively. The children presented in GDM group were excessively breast fed in comparison to other groups. However, the comparison was not significantly varied. The BMI, waist circumference and height of the obese children from both groups showed that children in GDM group were having increased waist circumference as well as decreased height and higher BMI values those non-GDM group children. There was a positive association of maternal GDM with childhood adiposity variations of childhood indicators specifically within the 6-9.5 years. Conclusion: Maternal GDM is a critical risk factor of obesity and overweight condition in childhood leading to a high frequency of obesity in children. Keywords: Association, Gestational diabetes, Childhood obesity